Temporomandibular Disorder Related Characteristics and Treatment Outcomes in Oromandibular Dystonia Patients in Two Different Clinical Settings: A Cross-Sectional Study - Sude, Asha (My University, 2020)
Introduction: Clinical presentation of oromandibular dystonia is variable and it can be further complicated with presence of TMD symptoms. We sought to evaluate variations in clinical presentation of OMD patients, particularly TMD related characteristics, in two clinic settings. Methods: In a cross-sectional study design, a web-based data collection survey was provided to eligible patients with OMD from Movement Disorder and Orofacial Pain clinics. Patients with OMD were identified using ICD-9 and ICD-10 diagnostic codes from their electronic health record system. We excluded patients <18 years old, pregnant women, prisoners, non-English speakers, patients with dementia, OMD diagnosis secondary to Parkinson’s disease and Tardive dyskinesia patients. The survey questionnaire was designed to collect information on demographic characteristics, clinical presentation particularly related to TMD, quality of life and treatment outcomes. Validated questionnaires were used when available such as TMD Screener, EQ-5D-5L, jaw functional limitation scale, and global rating of change scale. Results: Of 53 eligible patients; 31 responded to the survey for a 59% response rate. 48% patients in MD clinic and 60% patients in OFP clinic reported experiencing jaw pain along with involuntary movements. Of those, 90% from MD group and 83% from OFP group screened positive with TMD pain screener. TMD screener remained positive in about 40% patients in both clinics in the last 30 days of questionnaire response. Global score of JFLS was higher in both groups. None of the study comparisons between two groups were statistically significant. Conclusion: Patients with OMD have features of TMD, irrespective of the clinical setting they seek and receive care from. OMD patients from both clinics were similar in terms of clinical presentation, quality of life and treatment outcomes.
University of Minnesota M.S. thesis. 2020. Major: Dentistry. Advisor: Donald Nixdorf. 1 computer file (PDF); 40 pages.
Keywords: Oromandibular dystonia; Temporomandibular disorder